2015
DOI: 10.1186/s12904-015-0016-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergency visits among end-of-life cancer patients in Taiwan: a nationwide population-based study

Abstract: BackgroundAn increased number of emergency visits at the end of life may indicate poor-quality cancer care. The study aimed to investigate the prevalence and utilization of emergency visits and to explore the reasons for emergency department (ED) visits among cancer patients at the end of life.MethodsA retrospective cohort study was performed by tracking one year of ambulatory medical service records before death. Data were collected from the cancer dataset of Taiwan’s National Health Insurance Research Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
3
21
4
Order By: Relevance
“…In this study, we found that these factors associated with an increased risk of FA status: lower SES (housing subsidy type) and greater comorbidity. This was similar to the findings from other studies …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we found that these factors associated with an increased risk of FA status: lower SES (housing subsidy type) and greater comorbidity. This was similar to the findings from other studies …”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown FAs to have a higher chronic disease burden, lower SES, and higher utilization of nonemergency health care services . In a previous national cohort study, we found that certain cancer profiles increased the risk of ED FA: head and neck cancers were up to twice as likely to be an FA …”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…We included patients that had recently undergone curative oncologic treatment, rather than limiting the analyses to end‐of‐life patients. Furthermore, given the cohort size and diversity of diagnoses, we were able to divide the malignancies by specific diagnoses rather than collective groups such as “all gastrointestinal” cancers . This could account for the positive correlation between a diagnosis of esophageal, stomach, liver, pancreatic or biliary cancer and FA, as each of these was analyzed independently of neutral‐risk gastrointestinal cancers, such as colorectal cancer patients, which account for the largest group of gastrointestinal cancers in most populations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many cancer patients attend ED for issues unique to their diagnoses, stage, or treatment. Hence, several studies have focused on certain subgroups, such as end‐of‐life patients, and patients suffering from complications or side effects of chemotherapy, surgery, or radiotherapy …”
Section: Introductionmentioning
confidence: 99%